2016
DOI: 10.1002/jmv.24606
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and genetic diversity of group A rotavirus in acute diarrhea patients in pre‐vaccination era in southwest China

Abstract: Group A rotavirus (RVA) is one of the leading cause of acute diarrhea worldwide, the RVA-related disease burden and the genotypes of RVA is important reference to introduce RVA variance to national immunisation programmes, 1,121 diarrhea cases and 319 healthy controls were recruited from four sentinel hospital outpatient from July 2014 to June 2015. The prevalence of RVA was 244 (21.8%) in gastroenteritis cases and in 12 (3.8%) in healthy controls across all age group (OR = 7.12, 95%CI = 3.93-12.89); the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
5
11
0
Order By: Relevance
“…Symptoms including fever, vomiting, dehydration, and watery‐stool were frequent among children who tested positive for RVA as previous reported . There was no significant difference in the diarrhea frequency between RVA positive and negative groups ( P > .05), whereas vomiting, fever and respiratory symptoms were more frequent among children who were tested positive for RVA (71.37%, 27.9%, 43.47%, respectively) than among children who were tested negative for RVA (39.36%, 14.02%,32.03%, respectively, P < .001).…”
Section: Resultssupporting
confidence: 89%
“…Symptoms including fever, vomiting, dehydration, and watery‐stool were frequent among children who tested positive for RVA as previous reported . There was no significant difference in the diarrhea frequency between RVA positive and negative groups ( P > .05), whereas vomiting, fever and respiratory symptoms were more frequent among children who were tested positive for RVA (71.37%, 27.9%, 43.47%, respectively) than among children who were tested negative for RVA (39.36%, 14.02%,32.03%, respectively, P < .001).…”
Section: Resultssupporting
confidence: 89%
“…We found that the rate of diarrhea cases among the 4 age groups was significantly different; the prevalence of RVA was 24.0% (105/438) in the age group of 0-6 months, but it increased sharply to 38.0% (182/479) in the age group of 7-12 months, and then the detection rate of RVA declined continuously with increasing age. This conclusion was in keeping with previous studies [17][18][19]. We speculated that children under 6 months of age may obtain protective immunity against RVA.…”
Section: Discussionsupporting
confidence: 92%
“…G9P(8) (58.2%) had predominantly a G and P combination, and the total proportion of G9P(8), (4) 1 ( G3P (8), and G1P(8) being as high as 79.9% in all RVA strains in this study. A similar conclusion was obtained in other study [17]. In addition, the proportion of each genotype was not very different in several age groups, expect for G1P(4), which was more detected in diarrhea cases in the age group of 13-24 months.…”
Section: Discussionsupporting
confidence: 90%
“…Since then, G9 strains quickly spread worldwide and have been reported in Asia, Europe, and Africa . In China, the G9 RVA is commonly detected in patients and the environment . With a rapid incidence in recent years, G9 is now recognized as one of the most pandemic RVA strains.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] In China, the G9 RVA is commonly detected in patients and the environment. [12][13][14] With a rapid incidence in recent years, G9 is now recognized as one of the most pandemic RVA strains. These circulating G9 RVA strains have been reported in different phylogenetic lineages, with 11 sublineages within G9 and 4 lineages within P [8].…”
mentioning
confidence: 99%